Agronomic and technologic characteristics of common bean genotypes from Carioca commercial group - Lemos, Leandro Borges; de Oliveira, Ricardo Soares; Palomino, Edwin Camacho; da Silva, Tiago Roque Benetoli (Pesquisa Agropecuaria Brasileira, 2004)
Cultivars with high yield, adaptability and desirable technological characteristics are a must. The objective of this work was to evaluate agronomic and technologic characters of common bean genotypes from carioca commercial group. Genotypes were cultivated in water growing season, in 2001 and 2002. The experimental design was by randomized blocks with 29 genotypes and four replications. The IAC-Carioca, FT-Bonito, Rudá, Porto Real, CNFC 8008, CNFC 8011, CNFC 8012, CNFC 8013 and CNFC 8156 genotypes yielded above the average. The genotypes IAC-Carioca, CNFC 8012 and CNFC 8156 presented the best results with 3,000 kg ha-1 and 20 minutes cooking time.